The special education teachers’ ability to develop an integrated learning evaluation of Pancasila student profiles based on local wisdom for special needs students in Indonesia - Widana, I Wayan; Sumandya, I Wayan; Citrawan, I Wayan (Kasetsart Journal of Social Sciences, 2023)
This study aimed to analyze the special education teachers’ ability to develop an integrated learning evaluation of Pancasila student profile based on local wisdom for special needs students. The study was conducted in Bali, Nusa Tenggara Barat, and Nusa Tenggara Timur by using a mixed-method design. The first phase was done by using a quantitative approach. The sample selection used the cluster random sampling technique, with a total sample of 457 special education teachers. Data were collected using a questionnaire. In the second phase, the researchers used a qualitative approach. Informants were determined using purposive sampling and snowball sampling. Data were collected using in-depth interviews, observation, and document studies. All research data were analyzed using explanatory mixed-method analysis techniques. The results showed that the ability of special education teachers in the provinces of Bali, NTB, and NTT to develop an integrated learning evaluation of Pancasila student profile based on local wisdom for special needs students was in enough category. The variable of responsibility as a teacher (X1), the understanding of special education teachers on the basic concepts of learning evaluation (X2), understanding of the concept of the Pancasila student profile (X3), and understanding of local wisdom (X4) both partially and simultaneously have a positive and significant effect on the special education teachers’ ability in the provinces of Bali, NTB, and NTT to develop an integrated learning evaluation of Pancasila student profile based on local wisdom (Y) for special needs students.